2011
DOI: 10.1364/oe.19.026423
|View full text |Cite
|
Sign up to set email alerts
|

Fiber-pigtailed temperature sensors based on dielectric-loaded plasmonic waveguide-ring resonators

Abstract: We demonstrate optical fiber-pigtailed temperature sensors based on dielectric-loaded surface plasmon-polariton waveguide-ring resonators (DLSPP-WRRs), whose transmission depends on the ambient temperature. The DLSPP-WRR-based temperature sensors represent polymer ridge waveguides (~1×1 µm(2) in cross section) forming 5-µm-radius rings coupled to straight waveguides fabricated by UV-lithography on a 50-nm-thick gold layer atop a 2.3-µm-thick CYTOP layer covering a Si wafer. A broadband light source is used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Looking from another prospective, this means that the WRR transmission is sensitive to the ambient temperature, leading to the idea of a WRR-based temperature sensor. [ 197,198 ] The temperature variations of about ≈1 °C were monitored with the estimation of a minimal detectable level…”
Section: Other Applications Of Dlsppwsmentioning
confidence: 99%
“…Looking from another prospective, this means that the WRR transmission is sensitive to the ambient temperature, leading to the idea of a WRR-based temperature sensor. [ 197,198 ] The temperature variations of about ≈1 °C were monitored with the estimation of a minimal detectable level…”
Section: Other Applications Of Dlsppwsmentioning
confidence: 99%
“…In context with this, several shapes and different-sized NPs are studied. Various SPR-based temperature sensors were reported, using crystal fiber filled with silver nanowires, gold NP incorporated oxides, polymer-functionalized gold nanoprisms, dielectric-loaded plasmonic waveguide-ring resonators, and so on. SPR dependence on temperature for gold nanoparticle in silica matrix form 17–915 °C was studied by Yeshchenko et al Red shift, along with broadening of SPR band is observed in gold NP with increase in temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Numerical simulations have also been performed to understand the phenomenon and to help estimate the group index achieved in the fabricated double-resonator structures. Although the achieved group index is not high due to plasmonic resonator loss, the DRIT still provides a new means of waveguide dispersion control and we also expect that DRIT can find broad applications in the on-chip sensing area, e.g., in temperature sensing [15], because the induced transmission peaks in DRIT are more sensitive to index change.…”
mentioning
confidence: 99%